Masculine Face Wins?: Joint Effect of Crime Rate on Election Results (Revista Galega de Economía)
Extant management studies suggest that managers’ traits are closely linked to organizational behaviors and performance. Based on these findings, our study analyzed the effect of candidates’ facial masculinity on the general election results. This study conducted an empirical test based on the 21st South Korea Congressional Election data, analyzing individual masculinity as measured by the facial width-to-height ratio (fWHR) of 495 candidates. We also used the National Police Agency data to determine how the local crime rate moderates the correlation. Our multilevel models showed that candidates’ fWHR had an inverted U-shaped relationship with election results. Candidates who have masculine faces are more advantageous in the election. However, the percentage of votes decreased for candidates with too much an fWHR value. In addition, we found that the local crime rate moderates the relationship between candidates’ fWHR and election results. This study extends extant research by highlighting the joint effect of a person’s biological traits and political factors and finally provides an interesting managerial implication.